PENYELENGGARAAN PUSAT PENDIDIKAN DAN LATIHAN OLAHRAGA PELAJAR (PPLP) DI PROVINSI JAWA BARAT TAHUN 2009-2019 (Tinjauan Historis) - Dian Kurniawan, - (2021)
This study aims to obtain an overview regarding the development of PPLP in West Java Province in organizing training programs in improving the achievements of athletes who come from students during the last ten years. This study uses the historical method, which consists of heuristics, criticism, interpretation and historiography. This is consistent with the diachronic form of data (it has already happened). Researchers are placed as a key instrument with data collection techniques carried out through inductive data analysis.Historical research includes qualitative research, because it tries to describe an organizational development from data in the form of words, descriptions, and documents. Therefore, data collection techniques are in the form of literature studies and documentation as well as interviews. The rationale for using this method is because this research wants to know about existing phenomena and in natural conditions, not under controlled, metabolic or experimental conditions.This research answers the problem which consists of: what factors are behind the establishment of PPLP West Java? How was the management of West Java PPLP coaching before 2009? How is the management of West Java PPLP coaching in 2009-2019? How is the impact of management on athletes' performance in West Java? The results of the research are in the form of descriptions related to the development of PPLP in West Java since its establishment until today with leadership policies and programs that are the unit of analysis, thus describing the dynamics of policies / programs developed from 2009-2019 by observing the management function known as POAC (Planning, Organizing, Actuating and Controlling).This research is expected to be an input for policy makers about the importance of managing an organization that pays attention to management functions to improve the ability of coaches to foster athletes or even further to improve sports performance at the West Java level that can be adopted by similar organizations in Indonesia. Keywords: Management of sport, sport development, sport policy and development